The role of writing in psychosis - Borges, Sonia (Clinical Styles. The Journal on the vicissitudes of childhood, 2008)
In this article, I discuss the role of writing in the psychosis. As a reference, I've taken texts produced by Pedro for about ten years in a Writing Workshop destined to patients of the Federal University of Rio de Janeiro's Psychiatry Institute. The figure of the insane person with papers under his arm is really emblematic and it's not difficult to find archives with its writings in the psychiatric hospitals, but, there is little literature concerning this. The participation in the Workshop, as well as the reading of the filed texts, has been bringing me many questions. After all, what does writing mean to a psychotic?